Dog: A Friendly Pathway to Zoonoses - Pathak, A.; Kaphle, K. (Nepalese Veterinary Journal, 2019)
Canis lupus familaris (Dog); a companion animal or even considered man’s best friend is believed to have been living in harmony with humans since thousands of years. Recent discovery in Chauvet cave in France: foot print of 8-year-old boy alongside the paw print is believed to have been dated back to Paleolithic period. Reports even suggest that pet owners are less prone to high cholesterol and high blood pressure than the non-pet owners. However, dogs are also the major reservoir of various zoonotic infections. Several bacterial, viral or protozoal diseases that occur in human are transmitted from the dogs. Such diseases are known as zoonotic diseases. These diseases can be transmitted by simple contact with the infected dogs or by infected urine or feces, saliva or aerosols. Viral infections such as rabies and noro virus, bacterial infection such as pasteurellosis, salmonellosis, campylobacteriosis, leptospirosis and Methicillin-Resistant Staphylococcus aureus (MRSA) infections and protozoal infections like ancylostomiasis, toxocariasis and Dipylidium caninum infection are the most common zoonotic infections. This paper focuses on these diseases including information on signs and symptoms, mode of transmission and prevention of these diseases. As much as these infections are concerned, knowledge boosting of the pet owners regarding zoonotic disease along with proper hygiene and good sanitation practices could considerably decline the rate of zoonoses transmission and consequences.